The Role of Product Packaging in the Purchasing Decisions of Consumers of Coca Cola - Valda, Levina Aprilia; Malhotra, Bhavya; Gupta, Gautam; Binti Mohd. Zaki, Nur Zulaikha; Binti Mohamed Jawathu, Nur Jazilah; Zhou, Kuan; Yingtai, Yin; Yifei, Meng (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
The curved bottle, designed and patented by Coca-Cola, was created in 1916 and became the standard packaging bottle for Coca-Cola. Since then, Coca-Cola has made it possible for consumers to identify the brand by its signature red, ribbon typeface. This paper aims to examine the influence of Coca-Cola's packaging on consumers purchasing decisions. A quantitative research approach was adopted, utilizing an online survey conducted through Google Forms with a sample size of 150 respondents. The survey included five variables: Packaging Material, Packaging Design, Packaging Color, Packaging Font and Packaging Printed Information. Multiple regression analysis was employed to determine whether these variables have a significant impact on consumer purchase decisions. The findings of the study reveal that packaging material, packaging font, and packaging printed information have a positive and statistically significant impact on consumer purchasing decision of Coca Cola Product.